Ultrahigh molecular weight polyethylene material and application thereof in woven bag products

By mixing inorganic pigment and g-C3N4 powder in ultra-high molecular weight polyethylene, and melt spinning after liquid nitrogen treatment, the problems of low color fastness and poor mechanical properties in ultra-high molecular weight polyethylene braided bag products are solved, and high fracture strength and good pigment dispersion effect are achieved, which is suitable for wastewater treatment.

CN119800540AInactive Publication Date: 2025-04-11SIXIAN JINHUI PACKAGING TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510049916.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene has problems such as low color fastness, uneven coloring, and poor mechanical properties in woven bag products, especially in the spinning process, which is prone to the agglomeration of carbon black, resulting in broken wire and poor quality.

Method used

By mixing and dispersing the inorganic pigment and g-C3N4 powder in an organic solvent, adding ionic liquid and mixing it with molten ultra-high molecular weight polyethylene, cooling and processing by liquid nitrogen, finally melt spinning is obtained to obtain fibers with high breaking strength and good pigment dispersion effect.

Benefits of technology

It realizes the high breaking strength and good pigment dispersion effect of ultra-high molecular weight polyethylene fibers, avoids the wire breaking problem caused by carbon black agglomeration, and improves the resistance to strong acid color fastness, which is suitable for wastewater treatment in extremely harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800540A_ABST
    Figure CN119800540A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of woven bags, and particularly relates to an ultra-high molecular weight polyethylene material and application of the ultra-high molecular weight polyethylene material in woven bag products. 3-5 parts of an inorganic pigment; 0.6 to 1 part of g-C3N4 powder; 1-2 parts of an ionic liquid; and 15-25 parts of an organic solvent. When the inorganic pigment is added into the ultra-high molecular weight polyethylene, the inorganic pigment and the g-C3N4 powder are combined in the presence of an organic solvent, then the mixture is added into the molten ultra-high molecular weight polyethylene, liquid nitrogen treatment is performed after cooling, and finally melt spinning is performed to obtain the fiber. The inorganic pigment has a good dispersion effect in the ultra-high molecular weight polyethylene, the spinnability is good, the discoloring phenomenon is avoided, and the color fastness to strong acid can reach level 5; in addition, the composite material also has certain photocatalytic degradation performance on pharmaceutical wastewater such as diclofenac, and woven bag products prepared from the composite material are particularly suitable for sewage treatment in extremely severe environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of woven bags, and in particular relates to ultra-high molecular weight polyethylene materials and applications thereof in woven bag products. Background Art

[0002] In the field of special woven bags, ultra-high molecular weight polyethylene fibers, carbon fibers, aramid fibers, etc. can be used for weaving.

[0003] Ultra-high molecular weight polyethylene refers to unbranched linear polyethylene with a molecular weight of more than 1.5 million and a density of 0.920 to 0.964 g / cm 3 , heat deformation temperature (0.46MPa) 85℃, melting point 130~136℃.

[0004] At present, due to the molecular structure characteristics of ultra-high molecular weight polyethylene itself, the use of traditional printing and dyeing technology to color it has prominent problems such as low color fastness, uneven coloring, and poor mechanical properties.

[0005] If dyes are doped into ultra-high molecular weight polyethylene and then spun, the requirements for dyes are very high. For example, black dye carbon black, carbon black particles have a large specific surface area, and under the action of van der Waals gravity, particles are easily adsorbed and agglomerated; agglomeration is fatal to fibers, not only affecting the spinnability of the fibers, but also causing a large number of broken fibers during the spinning process; it also affects the quality of woven products made from the fibers. Specifically, a large amount of carbon deposits were found on the filter screen in the spinning box, indicating that a large number of carbon black particles agglomerated during the spinning process, resulting in carbon black seepage.

[0006] At present, the purpose of dyeing is generally achieved by spraying a colored coating on the surface of silk thread / woven fabric. However, the color integrity of woven fabrics is poor when using coating dyeing, and the spraying of silk thread is difficult and wastes a lot of paint.

[0007] Therefore, the dyeing problem of ultra-high molecular weight polyethylene is the key to solving its large-scale application in woven bag products. Based on this, the present invention is proposed. Summary of the invention

[0008] The object of the present invention is to provide an ultra-high molecular weight polyethylene material and its application in woven bag products to solve the above-mentioned problems.

[0009] In the first aspect, the ultra-high molecular weight polyethylene material, the raw materials of which include the following components in parts by weight:

[0010] Ultra-high molecular weight polyethylene, 100 parts; inorganic pigment, 3-5 parts; g-C3N4 powder, 0.6-1 parts; ionic liquid, 1-2 parts; organic solvent, 15-25 parts.

[0011] g-C3N4 powder, chemical formula g-C3N4, Chinese name: graphite-like carbon nitride.

[0012] In a further improvement, the ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate.

[0013] In a further improvement, the organic solvent is one or more of methanol, ethanol, acetone, and N,N-dimethylformamide.

[0014] In a further improvement, the inorganic pigment is one or more of titanium dioxide, carbon black, iron oxide series pigments, chromium series pigments, cadmium series pigments, and cobalt series pigments.

[0015] Common inorganic pigments are of the following types:

[0016] Titanium dioxide, carbon black.

[0017] Iron oxide series pigments: including iron oxide red, iron oxide yellow, iron oxide black, etc.

[0018] Chrome pigments: such as chrome green and chrome yellow.

[0019] Cadmium pigments: such as cadmium red and cadmium yellow.

[0020] Cobalt pigments: such as cobalt blue and cobalt green.

[0021] As a further improvement, the mass ratio of the inorganic pigment to the g-C3N4 powder is 5:1.

[0022] In a second aspect, a method for preparing an ultra-high molecular weight polyethylene material comprises the following steps:

[0023] Step 1, mix and disperse the g-C3N4 powder with an organic solvent, then add an inorganic pigment and continue to mix and disperse; then heat to boiling, add ionic liquid in batches to mix and disperse, keep boiling, and concentrate to obtain a first mixed material;

[0024] Step 2, heating the ultra-high molecular weight polyethylene to a molten state, then adding the first mixed material into the molten ultra-high molecular weight polyethylene, mixing evenly, and cooling to room temperature to obtain a second mixed material;

[0025] Step 3, breaking the second mixed material into pieces, and then impregnating it with liquid nitrogen, taking it out after impregnation, and crushing it to obtain a primary mixed powder;

[0026] Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

[0027] As a further improvement, in step 1, ultrasonic mixing and dispersion is adopted between g-C3N4 powder and organic solvent, and then inorganic pigment is added and ultrasonic mixing and dispersion is continued; the solid content in the first mixture is 52% to 55%.

[0028] As a further improvement, in step 2, the ultra-high molecular weight polyethylene is heated to 135-137° C. and is heated until the ultra-high molecular weight polyethylene is melted.

[0029] As a further improvement, in step 3, the liquid nitrogen immersion is performed for 12 to 15 minutes; and the particle size of the initial mixed powder is less than or equal to 1.18 mm.

[0030] The third aspect is the application of the ultra-high molecular weight polyethylene material in woven bag products.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] When adding inorganic pigments to ultra-high molecular weight polyethylene, the inorganic pigments and g-C3N4 powder are first combined in an organic solvent, then added to the molten ultra-high molecular weight polyethylene, cooled and treated with liquid nitrogen, and finally melt-spun. The obtained fiber has high breaking strength, good dispersion effect of the inorganic pigment in the ultra-high molecular weight polyethylene, good spinnability, no decolorization, and strong acid color fastness of up to level 5; in addition, it also has a certain photocatalytic degradation performance for medical wastewater such as diclofenac, and is made into woven bag products, which are particularly suitable for sewage treatment in extremely harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a photo of the ultra-high molecular weight polyethylene material in Example 7 when it is woven into a wire harness;

[0034] Figure 2 This is a curve showing the change in mass of g-C3N4 powder and maximum spinning speed. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0036] Example 1

[0037] Recipe 1:

[0038] Ultra-high molecular weight polyethylene, 1kg; inorganic pigment, 0.03kg; g-C3N4 powder, 0.006kg; ionic liquid, 0.01kg; organic solvent, 0.15kg.

[0039] The ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate, CAS number: 910247-97-1.

[0040] The organic solvent is ethanol. The inorganic pigment is carbon black.

[0041] The method for preparing the ultra-high molecular weight polyethylene material comprises the following steps:

[0042] Step 1: Ultrasonic mixing and dispersing g-C3N4 powder and organic solvent, then adding inorganic pigment, and continuing ultrasonic mixing and dispersing; then heating to boiling, adding ionic liquid in batches for mixing and dispersing, keeping boiling, concentrating, and obtaining a first mixture, wherein the solid content of the first mixture is 52%.

[0043] Step 2: Heat the ultra-high molecular weight polyethylene to 135-137° C. and keep heating until it melts, then add the first mixture into the molten ultra-high molecular weight polyethylene, mix well, and cool to room temperature to obtain a second mixture.

[0044] Step 3: Break the second mixed material into pieces, and then soak it in liquid nitrogen for 12 minutes. After the soaking is completed, take it out and crush it to obtain a primary mixed powder with a particle size of less than or equal to 1.18 mm.

[0045] Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

[0046] Example 2

[0047] Recipe 2:

[0048] Ultra-high molecular weight polyethylene, 1kg; inorganic pigment, 0.05kg; g-C3N4 powder, 0.01kg; ionic liquid, 0.02kg; organic solvent, 0.25kg.

[0049] The ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate, CAS number: 910247-97-1.

[0050] The organic solvent is ethanol. The inorganic pigment is carbon black.

[0051] The method for preparing the ultra-high molecular weight polyethylene material comprises the following steps:

[0052] Step 1: Ultrasonic mixing and dispersing g-C3N4 powder and organic solvent, then adding inorganic pigment and continuing ultrasonic mixing and dispersing; then heating to boiling, adding ionic liquid in batches for mixing and dispersing, keeping boiling, concentrating, and obtaining a first mixture, wherein the solid content of the first mixture is 55%.

[0053] Step 2: Heat the ultra-high molecular weight polyethylene to 135-137° C. and keep heating until it melts, then add the first mixture into the molten ultra-high molecular weight polyethylene, mix well, and cool to room temperature to obtain a second mixture.

[0054] Step 3: Break the second mixed material into pieces, and then soak it in liquid nitrogen for 15 minutes. After the soaking is completed, take it out and crush it to obtain a primary mixed powder with a particle size of less than or equal to 1.18 mm.

[0055] Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

[0056] Example 3

[0057] This example is different from Example 2 only in the added ionic liquid, which is 1-ethyl-2,3-dimethylimidazole bromide, CAS No.: 98892-76-3; the rest are the same.

[0058] Example 4

[0059] This example is different from Example 2 only in the added ionic liquid, which is 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate, CAS No.: 292140-86-4; the rest are the same.

[0060] Example 5

[0061] Recipe 3:

[0062] Ultra-high molecular weight polyethylene, 1kg; inorganic pigment, 0.06kg; ionic liquid, 0.02kg; organic solvent, 0.25kg.

[0063] The ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate, CAS number: 910247-97-1.

[0064] The organic solvent is ethanol. The inorganic pigment is carbon black.

[0065] The method for preparing the ultra-high molecular weight polyethylene material comprises the following steps:

[0066] Step 1: Mix and disperse the inorganic pigment and the organic solvent by ultrasonication, then heat to boiling, add the ionic liquid in batches for mixing and dispersion, keep boiling, and concentrate to obtain a first mixed material, wherein the solid content of the first mixed material is 54%.

[0067] Step 2: Heat the ultra-high molecular weight polyethylene to 135-137° C. and keep heating until it melts, then add the first mixture into the molten ultra-high molecular weight polyethylene, mix well, and cool to room temperature to obtain a second mixture.

[0068] Step 3: Break the second mixed material into pieces, and then soak it in liquid nitrogen for 15 minutes. After the soaking is completed, take it out and crush it to obtain a primary mixed powder with a particle size of less than or equal to 1.18 mm.

[0069] Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

[0070] In this example, after spinning, carbon deposits were found on the filter screen in the spinning box (the filter screen was cleaned before spinning and had no carbon deposits). This indicates that carbon black agglomeration still occurred. However, this phenomenon did not occur in Examples 1 and 2.

[0071] Example 6

[0072] Recipe 2:

[0073] Ultra-high molecular weight polyethylene, 1kg; inorganic pigment, 0.05kg; g-C3N4 powder, 0.01kg; ionic liquid, 0.02kg; organic solvent, 0.25kg.

[0074] The ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate, CAS number: 910247-97-1.

[0075] The organic solvent is ethanol. The inorganic pigment is carbon black.

[0076] The method for preparing the ultra-high molecular weight polyethylene material comprises the following steps:

[0077] Step 1: Ultrasonic mixing and dispersing g-C3N4 powder and organic solvent, then adding inorganic pigment, and continuing ultrasonic mixing and dispersing; then heating to boiling, adding ionic liquid in batches for mixing and dispersing, keeping boiling, concentrating, and obtaining a first mixture, wherein the solid content in the first mixture is 53%.

[0078] Step 2: adding ultra-high molecular weight polyethylene to the first mixed material, performing extrusion granulation at an extrusion temperature of 135-137° C., and obtaining pellets.

[0079] Step 3: The pellets are immersed in liquid nitrogen for 15 minutes. After the immersion is completed, they are fished out and crushed to obtain a primary mixed powder with a particle size of less than or equal to 1.18 mm.

[0080] Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

[0081] In this example, since the first compound is directly added to the ultra-high molecular weight polyethylene for extrusion granulation, compared with adding the first compound to the molten ultra-high molecular weight polyethylene, this method of this example will cause uneven dispersion and bring about a series of serious defects.

[0082] Example 7

[0083] The difference between this example and Example 2 is that the second mixed material is not rapidly cooled by liquid nitrogen, but is directly crushed to obtain a control preliminary mixed powder with a particle size of less than or equal to 1.18 mm. The control preliminary mixed powder is then melt-spun, cooled, stretched, and heat-set to obtain a fibrous ultra-high molecular weight polyethylene material.

[0084] Due to the molecular structure characteristics of ultra-high molecular weight polyethylene itself, and because the carbon black has not been treated with a coupling agent, the amount of carbon black added (based on ultra-high molecular weight polyethylene) exceeds 3%. In addition, foreign materials such as g-C3N4 powder and ionic liquid are added. If liquid nitrogen quick freezing is not performed, the serious entanglement between the molecular chains may cause a part of the carbon black to be enriched on the fiber surface in large quantities, which will cause the fibers in local areas to become seriously discolored.

[0085] In this example, the fibrous ultra-high molecular weight polyethylene material is spun and then woven into a bundle, such as Figure 1 As shown; when the wire harness is clamped with white paper and rubbed repeatedly, some black friction marks are found on the white paper. However, when the corresponding ultra-high molecular weight polyethylene materials in Examples 1 to 4 are woven into wire harnesses and rubbed with white paper, the above phenomenon is not found.

[0086] Example 8

[0087] The difference between this example and Example 2 is that in step 1, after the inorganic pigment and g-C3N4 powder are stirred and mixed, ethanol is added and ultrasonically dispersed, and then heated to boiling, ionic liquids are added in batches for mixing and dispersion, and boiling is maintained and concentrated to obtain a first mixed material, in which the solid content of the first mixed material is 54%. The rest is the same. Finally, after spinning, it was found that some carbon deposits were found on the filter screen in the spinning box (the filter screen was cleaned before spinning and there was no carbon deposit); this shows that carbon black agglomeration still occurs. This phenomenon does not occur in Example 1 and Example 2.

[0088] The properties of the ultra-high molecular weight polyethylene materials of Examples 1, 2, 3, 4, and 6 are shown in Table 1:

[0089] Table 1

[0090] Breaking strength (cN / dtex) Color fastness to dilute acid Color fastness to strong acid Example 1 33.25 Level 5 Level 5 Example 2 35.11 Level 5 Level 5 Example 3 29.87 Level 5 Level 5 Example 4 30.02 Level 5 Level 3 Example 6 18.15 Level 3 Level 1

[0091] The strong acid color fastness measurement is performed by immersing the fiber (such as the fibrous ultra-high molecular weight polyethylene material in Example 1) in a 65% by mass sulfuric acid solution in a high and low temperature circulation oven at a temperature of 5°C to 45°C for 96 hours; after the end, the fiber is washed with deionized water and dried, and the color fastness is measured with reference to GB / T 8427-2008.

[0092] Different from the measurement of color fastness to strong acid, the measurement of color fastness to dilute acid uses 10% sulfuric acid solution, and the rest are the same.

[0093] It can be seen from the above that the ultra-high molecular weight polyethylene materials prepared in Example 1 and Example 2 have high breaking strength and color fastness, especially the color fastness to strong acid can reach level 5.

[0094] Whether g-C3N4 powder is added and the order of addition will affect the dispersion effect of inorganic pigments in ultra-high molecular weight polyethylene.

[0095] The addition of 1,2,3-trimethylimidazole dimethyl phosphate and 1-ethyl-2,3-dimethylimidazole bromide as ionic liquids can also improve the color fastness of fibers to strong acids.

[0096] Example 9

[0097] Due to the high viscosity and long relaxation time of ultra-high molecular weight polyethylene, the spinning speed is limited during melt spinning. In the present invention, the combination of inorganic pigment and g-C3N4 will seriously affect the spinning speed.

[0098] Measurement of the maximum spinning speed: During spinning, the spinning speed is continuously increased until the yarn breaks three times in succession, and the minimum spinning speed when the yarn breaks occur is recorded.

[0099] In Example 2, the mass of the inorganic pigment remains unchanged (all 50 g), the mass of the g-C3N4 powder is 1 g, 5 g, 10 g, 15 g, and 20 g, respectively, and the corresponding maximum spinning speed change curve is shown in FIG. Figure 2 .

[0100] Depend on Figure 2 It can be seen that the optimal mass ratio of the inorganic pigment to g-C3N4 powder is 5:1.

[0101] Example 10

[0102] Photocatalytic degradation test

[0103] Weigh 0.5g of ultra-high molecular weight polyethylene material and soak it in a 15mg / L diclofenac solution. Perform a dark reaction to reach adsorption-desorption equilibrium. Then use LED visible light to irradiate, take samples every 20 minutes, filter and take the supernatant, and finally determine the concentration of diclofenac in the solution by high performance liquid chromatography.

[0104] Photocatalytic degradation rate = (initial concentration of diclofenac solution - concentration of diclofenac solution after degradation) / initial concentration of diclofenac solution; the concentration of diclofenac solution after degradation refers to the concentration of diclofenac in the solution measured by sampling once every 20 minutes; the maximum value of the photocatalytic degradation rate obtained is the maximum photocatalytic degradation rate.

[0105] The photocatalytic degradation test results of Examples 1 to 4, ultra-high molecular weight polyethylene, g-C3N4 powder, 1,2,3-trimethylimidazolium dimethyl phosphate, 1-ethyl-2,3-dimethylimidazolium bromide, and 1-ethyl-2,3-dimethylimidazolium hexafluorophosphate are shown in Table 2:

[0106] Table 2

[0107]

[0108]

[0109] It can be seen from Table 2 that after adsorbing carbon black, g-C3N4 powder is combined with 1,2,3-trimethylimidazole dimethyl phosphate to exert a larger number of active sites, thereby significantly improving its photocatalytic degradation performance for diclofenac.

[0110] Diclofenac is a commonly used anti-inflammatory drug. The ultra-high molecular weight polyethylene material of the present invention is made into a woven bag used in special fields, which has good strong acid resistance and high color fastness to strong acid. At the same time, it also has a certain photocatalytic degradation effect on diclofenac, and is particularly suitable for sewage treatment in extremely harsh environments.

[0111] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Ultra-high molecular weight polyethylene material, characterized by: The raw materials include the following components by weight: Ultra-high molecular weight polyethylene, 100 parts; inorganic pigment, 3-5 parts; g-C3N4 powder, 0.6-1 parts; ionic liquid, 1-2 parts; organic solvent, 15-25 parts.

2. The ultra-high molecular weight polyethylene material according to claim 1, characterized in that: The ionic liquid is 1,2,3-trimethylimidazole dimethyl phosphate.

3. The ultra-high molecular weight polyethylene material according to claim 1, characterized in that: The organic solvent is one or more of methanol, ethanol, acetone and N,N-dimethylformamide.

4. The ultra-high molecular weight polyethylene material according to claim 1, characterized in that: The inorganic pigment is one or more of titanium dioxide, carbon black, iron oxide series pigments, chromium series pigments, cadmium series pigments, and cobalt series pigments.

5. The ultra-high molecular weight polyethylene material according to claim 1, characterized in that: The mass ratio of the inorganic pigment to the g-C3N4 powder is 5:

1.

6. The method for preparing an ultra-high molecular weight polyethylene material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, mix and disperse the g-C3N4 powder with an organic solvent, then add an inorganic pigment and continue to mix and disperse; then heat to boiling, add ionic liquid in batches to mix and disperse, keep boiling, and concentrate to obtain a first mixed material; Step 2, heating the ultra-high molecular weight polyethylene to a molten state, then adding the first mixed material into the molten ultra-high molecular weight polyethylene, mixing evenly, and cooling to room temperature to obtain a second mixed material; Step 3, breaking the second mixed material into pieces, and then impregnating it with liquid nitrogen, taking it out after impregnation, and crushing it to obtain a primary mixed powder; Step 4: melt-spinning, cooling, stretching and heat-setting the primary mixed powder to obtain a fibrous ultra-high molecular weight polyethylene material.

7. The method for preparing the ultra-high molecular weight polyethylene material according to claim 6, characterized in that: In step 1, g-C3N4 powder and organic solvent are dispersed by ultrasonic mixing, and then inorganic pigment is added and ultrasonic mixing and dispersion are continued; the solid content in the first mixture is 52% to 55%.

8. The method for preparing the ultra-high molecular weight polyethylene material according to claim 6, characterized in that: In step 2, the ultra-high molecular weight polyethylene is heated to 135-137° C. and is heated until the ultra-high molecular weight polyethylene is melted.

9. The method for preparing the ultra-high molecular weight polyethylene material according to claim 6, characterized in that: In step 3, the mixture is immersed in liquid nitrogen for 12 to 15 minutes; the particle size of the initial mixed powder is less than or equal to 1.18 mm.

10. Use of the ultra-high molecular weight polyethylene material according to any one of claims 1 to 5 in woven bag products.

Citation Information

Patent Citations

  • Preparation method of graphite type carbon nitride-ionic liquid composite material

    CN103214878A

  • Functional-ionic-liquid-modified graphite C3N3 catalytic material, and preparation method and application thereof

    CN104475153A

  • Making method of ultrahigh molecular weight polyethylene colored fibers

    CN105133066A

  • Colored ultra-high molecular weight polyethylene fiber and preparation method thereof

    CN106245136A

  • Ionic liquid functional carbon nitride nanosheet modified electrode as well as preparation and application of electrode in chlorphenol detection

    CN106442666A